Does CD4+CD25+foxp3+ cell (Treg) and IL-10 profile determine susceptibility to immune reconstitution inflammatory syndrome (IRIS) in HIV disease? - Shankar, Esaki Muthu (BioMed Central, 2008)
HIV-specific T-lymphocyte responses that underlie IRIS are incomplete and largely remain hypothetical. Of the several mechanisms presented by the host to control host immunological damage, Treg cells are believed to play a critical role. Using the available experimental evidence, it is proposed that enormous synthesis of conventional FoxP3(- )Th cells (responsive) often renders subjects inherently vulnerable to IRIS, whereas that of natural FoxP3(+ )Treg cell synthesis predominate among subjects that may not progress to IRIS. We also propose that IRIS non-developers generate precursor T-cells with a high avidity to generate CD4+CD25+FoxP3+ Tregs whereas IRIS developers generate T-cells of intermediate avidity yielding Th0 cells and effector T-cells to mediate the generation of proinflammatory cytokines in response to cell-signaling factors (IL-2, IL-6 etc.). Researchers have shown that IL-10 Tregs (along with TGF-β, a known anti-inflammatory cytokine) limit immune responses against microbial antigens in addition to effectively controlling HIV replication, the prime objective of HAART. Although certain technical limitations are described herein, we advocate measures to test the role of Tregs in IRIS.